Eryptotic Phenotype in Chronic Myeloid Leukemia: Contribution of Neutrophilic Cathepsin G - Rukmini Govekar; Poonam Kawle; Renjan Thomas; Suresh Advani; Sheena PV; Surekha Zingde (Anemia, 2012)
In pathological conditions with concurrent neutrophilia, modifications of erythrocyte membrane proteins are reported. In chronic myeloid leukemia (CML), a myeloproliferative disease wherein neutrophilia is accompanied by enhanced erythrophagocytosis, we report for the first time excessive cleavage of erythrocyte band 3. Distinct fragments of band 3 serve as senescent cell antigens leading to erythrophagocytosis. Using immunoproteomics, we report the identification of immunogenic 43 kDa fragment of band 3 in 68% of CML samples compared to their detection in only 38% of healthy individuals. Thus, excessive fragmentation of band 3 in CML, detected in our study, corroborated with the eryptotic phenotype. We demonstrate the role of neutrophilic cathepsin G, detected as an immunogen on erythrocyte membrane, in band 3 cleavage. Cathepsin G from serum adsorbs to the erythrocyte membrane to mediate cleavage of band 3 and therefore contribute to the eryptotic phenotype in CML.